2017
DOI: 10.1007/s41105-017-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bedtime periocular and posterior cervical cutaneous warming on sleep status in adult male subjects: a preliminary study

Abstract: Appropriate warming of the periocular or posterior cervical skin has been reported to induce autonomic or mental relaxation in humans. To clarify the effects of cutaneous warming on human sleep, eight male subjects with mild sleep difficulties were asked to try three experimental conditions at home, each lasting for 5 days, in a cross-over manner: warming of the periocular skin with a warming device for 10 min before habitual bedtime, warming of the posterior cervical skin with a warming device for 30 min befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 26 publications
3
19
2
Order By: Relevance
“…Our results are comparable with our previous findings that periocular warming before bedtime improved subjective sleep initiation and enhanced delta power in the first 90-min period of the nocturnal sleep 23 . The results obtained through qualitive and quantitative EEG analyses in the present study clearly indicated that periocular skin warming accelerated and deepened non-rapid eye movement (NREM) sleep.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results are comparable with our previous findings that periocular warming before bedtime improved subjective sleep initiation and enhanced delta power in the first 90-min period of the nocturnal sleep 23 . The results obtained through qualitive and quantitative EEG analyses in the present study clearly indicated that periocular skin warming accelerated and deepened non-rapid eye movement (NREM) sleep.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is not clear which location on the human skin is most effective to promote sleep. Previous 22 , 23 studies and present study have showed that appropriate periocular skin warming has favorable effects on sleep. We postulate that the periocular skin region might be regarded as one closest regions of the eyes which is directly connected to the brain.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations